2020
DOI: 10.1093/jee/toaa273
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq Analysis Reveals Mitochondrial and Cuticular Protein Genes Are Associated with Phosphine Resistance in the Rusty Grain Beetle (Coleoptera:Laemophloeidae)

Abstract: The rusty grain beetle, Cryptolestes ferrugineus (Stephens), is a serious pest of stored grain, which has developed high levels of resistance to phosphine. In this study, five geographically distant populations of C. ferrugineus had been collected in China, specifically in granaries where phosphine fumigant is used for pest control, and they showed a high resistance ratio up to 1,907 (LC50 = 21.0 mg/liter). Then, a reference transcriptome was constructed to use as a basis for investigating the molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…Generally, high hydrocarbon concentrations in relation to insecticide resistance are associated with thick cuticles [6,7,45]. In another study, transcriptomic findings for PH 3 -resistant Cryptolestes ferrugineus (Stephens) revealed significant enrichment of mitochondrial and cuticular protein genes [12], mirroring our results (Fig. 3).…”
Section: Transcriptomic Analysis Of Genes Expressed In Ph 3 -Suscepti...supporting
confidence: 88%
“…Generally, high hydrocarbon concentrations in relation to insecticide resistance are associated with thick cuticles [6,7,45]. In another study, transcriptomic findings for PH 3 -resistant Cryptolestes ferrugineus (Stephens) revealed significant enrichment of mitochondrial and cuticular protein genes [12], mirroring our results (Fig. 3).…”
Section: Transcriptomic Analysis Of Genes Expressed In Ph 3 -Suscepti...supporting
confidence: 88%
“…The down-regulation of some Cardinium -responsive miRNAs enchanced the cuticle proteins in whitefly Bemisia tabaci (Gennadius) biotype Q and modulated insect reproduction and growth ( Li et al, 2018 ). In addition, RNA-seq of Cryptolestes ferrugineus individuals from phosphine susceptible and resistant populations revealed the significantly increased expression levels of nine cuticular protein genes in the resistance population, demonstrating that the cuticular protein genes might be related to phosphine resistance ( Chen et al, 2021 ). In the current study, the target genes of identified differentially expressed miRNAs, especially the chitinase and cuticle protein, might involved in the insects immune response and the detoxification of xenobiotics including the Bt Cry1Ac toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the mixture of CPs, they greatly contribute to determine the properties of the insect cuticles for defending against environmental stresses [16,17]. Previous reports have shown that the changed expression of CP genes is associated with the exposure to insecticides, indicating that CPs participate in insecticide resistance [18][19][20][21]. However, the precise roles served by CPs in response to insecticides remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%